2011
DOI: 10.1007/s11262-011-0576-x
|View full text |Cite
|
Sign up to set email alerts
|

Complete genomic characterization of cell culture adapted human G12P[6] rotaviruses isolated from South Korea

Abstract: Two unusual human rotavirus G12 strains, CAU195 and CAU214, were isolated from female pediatric diarrhea patients under 12 months of age in 2006 using a cell culture system and their full genome sequences were analyzed. The 11 gene segments of both Korean G12 strains were classified as G12-P[6]-R1-C1-M1-I1-A1-N1-T1-E1-H1 genotypes. Notably, the Korean strains were of the same genotypes as previously reported strains isolated from Bangladesh in 2003 (Dhaka12-03), from the United States in 2005-2006 (US6597), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The GCRV dsRNA was extracted from a fecal sample by using Trizol (Gibco BRL, Grand Island, NY) according to the manufacturer's instructions. To obtain full‐length sequences of the 11 gene segments, the primers were obtained from the study of Yamamoto et al [], and the RT‐PCR reaction was carried out as previously described [Than et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…The GCRV dsRNA was extracted from a fecal sample by using Trizol (Gibco BRL, Grand Island, NY) according to the manufacturer's instructions. To obtain full‐length sequences of the 11 gene segments, the primers were obtained from the study of Yamamoto et al [], and the RT‐PCR reaction was carried out as previously described [Than et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…2A ) 54 , 63) . Phylogenetic analysis of all 11 gene sequences revealed that these genotypes belonged to genogroup I of the Wa-like genotype constellation 64) . These results suggest that G12 genotypes not only are persistent but also may have adapted and evolved in the South Korean population.…”
Section: Clinical Significance Of Unusual G Genotypes In South Koreamentioning
confidence: 99%